Pengaruh Kondusivitas Lingkungan Kerja Terhadap Kinerja Karyawan yang Dimediasi oleh Motivasi pada Hotel Sapodilla Ubud - Putra, I Made Junedi (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this research is to determine the impact of workplace conduciveness on employee performance, mediated by motivation, at Hotel Sapodilla Ubud. All members of the population were involved as respondents using a census approach. Data collection was carried out through observation, interviews, recording, and questionnaires. A five-point Likert scale was applied for measurement. The instrument testing was conducted using validity and reliability tests. The data analysis method used was path analysis. The findings of the study indicate that workplace conduciveness has a significant and positive effect on employee performance at Hotel Sapodilla Ubud. Workplace conduciveness also has a significant and positive effect on motivation at Hotel Sapodilla Ubud. Motivation has a significant and positive effect on employee performance at Hotel Sapodilla Ubud. Moreover, motivation mediates the impact of workplace conduciveness on employee performance at Hotel Sapodilla Ubud. The recommendations include enhancing collaboration among employees and fostering harmonious relationships between employees